3D Porous Nanoarchitectures Derived from SnS/S‐Doped Graphene Hybrid Nanosheets for Flexible All‐Solid‐State Supercapacitors. Issue 12 (16th January 2017) - Liu, Chunyan; Zhao, Shulin; Lu, Yanan; Chang, Yingxue; Xu, Dongdong; Wang, Qi; Dai, Zhihui; Bao, Jianchun; Han, Min
Abstract : 3D porous nanoarchitectures derived from SnS/S‐doped graphene hybrid nanosheets are successfully prepared by controllable thermal conversion of oleylamine‐capped mixed‐phase SnS2 ‐SnS nanodisks precursors, and employed as electroactive material to fabricate flexible, symmetric, all‐solid‐state supercapacitors. The fabricated solid devices exhibit very high areal specific capacitance (2.98 mF cm −2 ), good cycling stability (99% for 10 000 cycles), excellent flexibility, and desirable mechanical stability.